Application Of Feeding Rules And Tui Na Massage To Overcome Eating Difficulties In Toddlers - Yuliana, Fitri; Rahmah, Elfa Olivia; Darsono, Putri Vidiasari; Kusvitasari, Hairiana (JKM (Jurnal Kebidanan Malahayati), 2025)
Background: Decreased appetite or difficulty eating in toddlers can have an impact on the growth and development stages because during this period nutrition is very much needed for daily activities. Symptoms of difficulty eating can occur in around 60.3% of toddlers aged 2-3 years so that to overcome this problem, structured eating rules are needed so that parents have guidance in feeding their children, in addition toddlers also need to get touch in the form of massage to facilitate digestion and blood circulation so that appetite increases and nutrient absorption in the body becomes more optimal.Objective: Analyzing the application of feeding rules and tui na massage to eating difficulties in toddlers aged 2-3 years.Methods: This type of research is Pre-experimental with a one group pretest posttest design, the target of this research is 15 toddlers who have difficulty eating, the instruments used are questionnaires and checklists, then the data is analyzed using the Wilcoxon test.Signed Rank Test.Results: The nutritional status of toddlers who experience eating difficulties is on average in the normal category (80%), the application of feeding rules and tui na massage has a significant effect on reducing eating difficulties in toddlers with test resultsWilcoxon Signed Rank Testobtained a Sig. value (2-tailed) of 0.001 which is smaller than 0.05, after being given treatment, eating difficulties in toddlers decreased by 80%.Conclusion: Based on the research results, it can be concluded that the combination of optimal application of feeding rules by parents and tui na massage can be used as an alternative solution in overcoming eating difficulties in toddlers, because toddlers' meal schedules become more structured, helping to train proper eating regulation and helping toddlers become more relaxed and sleep better. Keywords: Difficulty Eating, Feeding Rules, Tui Na Massage  ABSTRAK : PENERAPAN FEEDING RULES DAN PIJAT TUI NA UNTUK MENGATASI KESULITAN MAKAN PADA BALITA Latar Belakang: Penurunan nafsu makan atau kesulitan makan pada balita dapat berdampak pada tahapan tumbuh kembang karena pada periode tersebut nutrisi sangat diperlukan untuk aktivitas sehari-hari. Gejala kesulitan makan dapat terjadi sekitar 60,3% pada balita usia 2 – 3 tahun sehingga untuk mengatasi permasalahan tersebut, perlu aturan makan terstruktur agar orangtua memiliki panduan dalam memberikan makan pada anak, selain itu balita juga perlu mendapatkan sentuhan dalam bentuk pijat agar memperlancar pencernaan dan peredaran darah agar nafsu makan meningkat dan serapan nutrisi dalam tubuh menjadi lebih optimal.Tujuan: Menganalisis penerapan feeding rules dan pijat tui na terhadap kesulitan makan pada balita usia 2-3 tahun.Metode: Jenis penelitian ini adalah Pre-experimental dengan rancangan one group pretest posttest, sasaran penelitian ini yaitu balita yang mengalami kesulitan makan sebanyak 15 orang, instrumen yang digunakan adalah kuesioner dan daftar tilik, kemudian data dianalisis menggunakan uji Wilcoxon Signed Rank Test.Hasil: Status gizi balita yang mengalami kesulitan makan rata-rata dalam kategori normal (80%), penerapan feeding rules dan pijat tui na berpengaruh signifikan terhadap penurunan kesulitan makan pada balita dengan hasil uji Wilcoxon Signed Rank Test diperoleh nilai Sig. (2-tailed) sebesar 0,001 lebih kecil dari 0,05, setelah diberikan perlakuan kesulitan makan pada balita mengalami penurunan sebesar 80%.Simpulan: Berdasarkan hasil penelitian dapat disimpulkan bahwa kombinasi penerapan feeding rules oleh orangtua secara optimal dan pijat tui na dapat dijadikan sebagai alternatif solusi dalam mengatasi kesulitan makan pada balita, karena jadwal makan balita menjadi lebih terstruktur, membantu melatih regulasi makan yang tepat dan membantu balita menjadi lebih rileks, serta tidur lebih nyenyak. Kata Kunci: Feeding Rules, Kesulitan Makan, Pijat Tui Na